Dilution of Eco Enzyme and Antimicrobial Activity Against Staphylococcus aureus - Ginting, Nurzainah; Hasnudi, Hasnudi; Yunilas, Yunilas; Prayitno, Lilik (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
Staphlylococcus aureus is pathogenic bacteria which causes mastitis. The objective of this study is to examine dilution of Eco Enzyme against Staphylococcus aureus. Research design was Completely Randomized Design with three scenarios of diluted Eco Enzyme: T1 = 1: 100 Eco Enzyme dilution; T2 = 1: 200 dilution; and T3 = 1: 300 dilution, using three parameters: antimicrobial zone of inhibition (mm), antimicrobial index (mm), and pH.  Eco Enzyme was produced from the fermentation of fruits containing enzymes, organic acids and microbial. The Eco Enzyme is applied, among others, as biodesinfectant in animal sheds. The results showed that Eco Enzyme either with 1:100, 1:200, or 1:300 concentrations has been proven to be able to inhibit Staphylococcus aureus. Meanwhile, the 1:100 dilution showed a strong inhibition.Keywords: animal sheds, bacteria, biodesinfectant, eco enzyme, mastitis